Pengaruh Subtitusi Cangkang Telur Ayam Ras pada Pupuk Feses Kambing terhadap Tanaman Rumput Gajah Fase Vegetative: The Effect of Chicken Eggshell Substitution in Goat Feces Fertilizer on Elephant Grass Plants in the Vegetative Phase - Syukri, Haeril; Bonewati, Yulia Irwina; Maryam, Maryam (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2026)
Background: Elephant grass (Pennisetum Purpureum) is a forage plant that plays a very important role, because it contains almost all the substances needed by animals. Purpose:  This study aims to determine the effect of adding chicken eggshells to goat feces fertilizer on elephant grass plants in the vegetative phase. Methods:  This study was conducted using a Completely Randomized Design (CRD), with 5 treatments and 4 replications. (P0: not using eggshell powder), (P1: 15g eggshell powder + 300g goat feces), (P2: 30g eggshell powder + 300g goat feces), (P3: 45g eggshell powder + 300g goat feces), (P4: 60g eggshell powder + 300g goat feces), The parameters measured in this study were plant height, number of tillers, number of leaves and leaf width. Results: The study showed that, (1) plants with the provision of eggshell powder had a significant effect (P<0.05) on plant height (2) the provision of eggshell powder did not have a significant effect (P>0.05) on the number of tillers, (3) eggshell powder had a significant effect (P<0.05) on the number of leaves, (4) and the provision of broiler eggshell powder did not have a significant effect on elephant grass plants on leaf width. Conclusion: Based on the average value, the effect of adding broiler eggshells to goat feces fertilizer in the treatments (P1–P4) every week provided better growth and development compared to the control treatment (P0).